'Spontaneous Virtual Mobility' in translation and interpreting: results from an exploratory project. Issue 2 (3rd May 2016) - Morón-Martín, Marián
ABSTRACT: Universities today offer a whole new range of learning opportunities for translation students. One of these is virtual mobility (VM), conceived as the phenomenon that arises when foreign students visiting under academic mobility programmes share learning spaces with local students at the partner institution. This article presents the main results of a descriptive exploratory project aimed at analysing the impact of VM in the training of translation students. Given the value of mobility nowadays, and its reported gains in terms of competence development, this article intends to promote further reflection on students' perceptions in terms of specific learning outcomes and to encourage trainers to analyse and self-assess their teaching practices when confronting VM environments. This is one of the first studies on this issue, and hence also intends to establish the basis for future research in this line.